Beyond social democracy the transformation of the left in emerging knowledge societies - Häusermann, Silja 1977-; Kitschelt, Herbert 1955- (Cambridge University Press, 2024)
"Explores how social democratic parties can win back voters and articulate their ideas through other party channels. This book addresses the core of debates within social democratic parties and left parties more broadly conceived. This title is also available as Open Access on Cambridge Core."
Literaturverzeichnis: Seite 423-457
Keywords: Politik; Sozialdemokratische Partei; Sozialdemokratie; Socialist parties / Europe; Politics, Practical / Europe; Party affiliation / Europe; Knowledge economy / Political aspects / Europe; Europe / Politics and government / 21st century; Aufsatzsammlung